Practitioner Learning Curve in Fitting Scleral Lenses in Irregular and Regular Corneas Using a Fitting Trial. - Macedo-de-Araújo, Rute J.; van der Worp, Eef; González-Méijome, José M. (BioMed Research International, 2019)
Purpose. To assess the learning curve of a novel practitioner with minor previous experience with scleral lenses (SL) fitting in the initial 156 consecutive fittings in irregular and regular corneas using a fitting trial. Methods. Prospective dispensing case series involving a total of 85 subjects (156 eyes), 122 eyes with irregular corneas (IC Group) and 34 eyes with regular corneas (RC Group). All lenses were fitted by the same practitioner with minimal previous knowledge and practice on SL fitting. The first 156 consecutive fits were studied to estimate the number of trial lenses required to achieve the optimal fit and the number of reorders required. The results were divided into 8 chronological groups of 20 fittings (eyes) each. Results. There was a decrease in the number of trial lenses required to achieve the optimal fit from 2.35±0.18 lenses in the first 20 fittings to 1.56±0.13 in the last fittings (p<0.05, Wilcoxon). There were no statistically significant differences between IC and RC groups. Regarding the number of reorders, there was also a decrease from 0.95±0.17 in the first fittings to 0.25±0.11 in the last fittings (p<0.05, Wilcoxon). Thought not statistically significant, there was an increase in the use of toric designs with increasing experience. Conclusions. Practitioner fitting experience reduced both the number of trial lenses required to achieve the best fit and the number of reorders with time. After the first 60 cases, there was a significant reduction in the trial lenses and reorders necessity.